Benefits of a one health approach: An example using Rift Valley fever - Melinda K. Rostal; Noam Ross; Catherine Machalaba; Claudia Cordel; Janusz T. Paweska; William B. Karesh (One Health, 2018)
One Health has been promoted by international institutions as a framework to improve public health outcomes. Despite strong overall interest in One Health, country-, local- and project-level implementation remains limited, likely due to the lack of pragmatic and tested operational methods for implementation and metrics for evaluation. Here we use Rift Valley fever virus as an example to demonstrate the value of using a One Health approach for both scientific and resources advantages. We demonstrate that coordinated, a priori investigations between One Health sectors can yield higher statistical power to elucidate important public health relationships as compared to siloed investigations and post-hoc analyses. Likewise, we demonstrate that across a project or multi-ministry health study a One Health approach can result in improved resource efficiency, with resultant cost-savings (35% in the presented case). The results of these analyses demonstrate that One Health approaches can be directly and tangibly applied to health investigations. Keywords: One health, Study design, Resource efficiency, Public health, Epidemiology, Outbreak investigation